2010
DOI: 10.1001/jama.2010.1862
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Leukemic Stem Cell Gene Expression Signature With Clinical Outcomes in Acute Myeloid Leukemia

Abstract: CUTE MYELOID LEUKEMIA(AML) is an aggressive malignancy of the bone marrow characterized by accumulation of early myeloid blood cells that fail to mature and differentiate. The course of the disease is marked by poor prognosis, frequent relapse, and high disease-related mortality. 1,2 Recent clinical investigation has focused on the identification of prognostic subgroups in adult AML with the goal of guiding patients into risk-adapted therapies. Such investigation determined that cytogenetic abnormalities are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
328
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(353 citation statements)
references
References 62 publications
22
328
1
2
Order By: Relevance
“…Since these LSC -particularly in their dormant stage -may survive treatment and give rise to subsequent relapse [19,[28][29][30][31][32][33][34][35][36][37][38][39]. The latter idea is supported by a recent study showing that a higher level of putative CD34 + /CD38 --LSC is associated with a worse prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Since these LSC -particularly in their dormant stage -may survive treatment and give rise to subsequent relapse [19,[28][29][30][31][32][33][34][35][36][37][38][39]. The latter idea is supported by a recent study showing that a higher level of putative CD34 + /CD38 --LSC is associated with a worse prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, also Gentles et al 38 defined a leukemic stem cell gene expression signature and found this signature to be strongly associated with clinical outcome in AML. The LSC signature identified by Gentles et al was shown to be highly expressed not only in leukemic, but also in normal hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…These were 28 stem cell specific genes and 20 progenitor cell specific genes. 25 Since we found that K4 was the most reliable marks of gene expression, we focused on loss and gain of K4 enrichment upon differentiation. In P10 AML cells, we found that 5 out of 28 (18%) stem cell-expressed genes had only K4 marks in stem cells that were lost in progenitor cells compared with only 1 out of 20 progenitor cell-expressed gene (5%) (Fig.…”
Section: Chromatin Immunoprecipitation-sequencing (Chip-seq)mentioning
confidence: 99%
“…This was most striking for bivalent genes that decreased to less than half of those in stem cells only, K27 only, bivalent, and bi-negative. Using publicly available AML stem and progenitor expression patterns (accession number GSE24006), 25 we categorized genes depending on their expression into high, intermediate, and low in stem and progenitor cells, and correlated these with K4 and K27 peaks (Fig. 3A).…”
Section: Chromatin Immunoprecipitation-sequencing (Chip-seq)mentioning
confidence: 99%